2009
DOI: 10.1158/0008-5472.sabcs-6099
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative breast cancer and obesity in a rural Appalachian population.

Abstract: #6099 Background: Our objective was to determine the clinico-pathological features of triple-negative (estrogen, progesterone and HER-2 receptor negative) breast cancer and their relationship to obesity in women drawn from a population with one of the highest obesity rates in the United States.
 Methods: This retrospective study involved 620 white patients with invasive breast cancer in West Virginia. Hospital tumor registry, charts, and pathology records provided age at diagnosis, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 0 publications
3
40
2
1
Order By: Relevance
“…Obesity has been proposed as a possible contributing factor. 9,10,12,14,22 We observed that race remained a significant predictor of triple-negative subtype, independent of BMI. With respect to the relation between BMI and tumor subtype, several smaller studies have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Obesity has been proposed as a possible contributing factor. 9,10,12,14,22 We observed that race remained a significant predictor of triple-negative subtype, independent of BMI. With respect to the relation between BMI and tumor subtype, several smaller studies have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 55%
“…5,[8][9][10][11][12][13] Patients with triple-negative cancers tend to present at a younger age and with more advanced cancer; however, the contribution of tumor subtype to the risk of lymph node involvement is less well defined. 4,6,14 With respect to patterns of recurrence, central nervous system (CNS) disease is a concern. 15, 16 The identification of factors associated with the triple-negative subtype is hampered by the absence of data on large populations.…”
Section: Introductionmentioning
confidence: 99%
“…Strong scientific evidence indicated that modifiable lifestyle factors such as alcohol consumption and obesity are associated with increased risk of breast cancer prognosis and contribute to inferior outcomes. [41][42][43][44][45] Lower percentage of surveyed pharmacists recognised obesity and alcohol intake as potential risk factors to develop breast cancer suggesting deficient knowledge. Insufficient knowledge of breast cancer screening recommendations among community pharmacists in Jordan can be explained, in part, by lacking attendance of continuous education programmes and inadequate undergraduate training.…”
Section: Discussionmentioning
confidence: 99%
“…Even if only six studies provided information on the percentage of patients taking propranolol or other drugs, there was some evidence that the effect of propranolol is stronger than those of other BB drugs, in agreement with both previous preclinical 24 and clinical studies. 14 Another possible heterogeneity source is the target population: patients with triple-negative BC have been shown to have higher prevalence of abdominal obesity and metabolic syndrome in some studies, 42,43 which have been linked to increased activation of the stress response pathway and disruption of the Sympathetic Nervous System axis. 44,45 This putative link coupled with the high expression of beta-ARs in triple-negative BC cell lines point to a potential role for BB in triple-negative BC treatment 46,47 which was highlighted in previous studies.…”
Section: Discussionmentioning
confidence: 99%